The fractional utilisation of maximal oxygen consumption during execution of groundstrokes and simulated match in 14 to 18 years state-level singles tennis players - Morazuki, Syahrul Ridhwan (2007)
The purpose of the present study was to determine the fractional utilisation of maximum oxygen uptake capacity(% V02max) during execution of groundstrokes and tennis match play. Ten male state-level tennis players participated in this study. Age, height, weight and V02max of the players were 15.3 + 1.2 years, 164.0 ± 7.4 em, 52.3 + 11.5 kg and 51.7 ± 7.3 ml·kg-1·min-1 respectively. This study was conducted in 3 phases: laboratory test (Phase 1), on-court test (Phase II) and simulated match (Phase Ill). Fractional utilisation of V02max during execution of forehand and backhand strokes were 67.1 + 15.2% and 70.3 + 13.6% respectively, whereas tennis match play demanded 69.3 + 9.8% of V02max· Execution of forehand and backhand strokes led to a blood lactate concentration of approximately 6 mmoi·L-1, indicating the involvement of anaerobic glycolytic supply of energy. On the other hand, due to intermittent nature of the game and the workrest ratio of 1 : 2.2, the post-match blood lactate was found to be 3.21 + 0.2 mmoi·L-1, reflecting an aerobic dominance of the game. It might be possible that the blood lactate was removed and was utilised during the rest pauses which were 2 times more than the work duration. Even the mean match heart rate (154.3 ± 15.4 beats·min-1) was lower than mean anaerobic threshold heart rate (164.7 + 5.7 beats·min-1), signifying a lower blood lactate level less than 4.0 mmoi·L-1 in a tennis match. Video analysis of the matches revealed that the players executed more forehand strokes (P<0.001) than the backhand strokes. Since similar heart rate and V02 responses were observed for forehand and backhand strokes, it is suggested that the players should train themselves equally on both groundstrokes. During the longest rally, mean heart rate of the players was 17 4.9 + 3.1 beats·min-1 , which corresponded to 84.5 ±. 2.2% of V02max· In addition, rallies per game, mean rally duration and strokes per rally were found to be 5. 7 + 2.4, 4.5 ±. 1.5 seconds and 2.8 + 0.8 shots respectively. This study concluded that the Kelantan state-level tennis players possessed a moderately good aerobic capacity. This can be improved to the international standard through endurance and intermittent type of training. Improvement in V02max may increase the playing intensity of the match as well a better recovery in the rest pauses and also delay the onset of fatigue during tennis play. From video match analysis and the heart rate and V02 relationship, it is suggested that the players should also improve the alactic anaerobic component through short burst of repeated movements of 5-8 seconds durations. XV